Gyōnen's transmission of the Buddha dharma in three countries - Green, Ronald S. (Numen Book Series, 2018)
Gyōnen's Transmission of the Buddha Dharma in Three Countries is the first English translation of this work and a new assessment of it. Gyōnen (1240-1321) has been recognized for establishing a methodology for the study of Buddhism that would come to dominate Japan. The three countries Gyōnen considers are India, China and Japan. Ronald S. Green and Chanju Mun describe Gyōnen's innovative doctrinal classification system ( panjiao ) for the first time and compare it to other panjiao systems. They argue that Gyōnen's arrangement and what he chose to exclude served political purposes in the Kamakura period, and thus engage current scholarship on the construction of Japanese Buddhism.